Understanding gender roles and practices in the household and on the farm: Implications for banana disease management innovation processes in Burundi - Iradukunda, F.; Bullock, Renee; Rietveld, Anne M.; Schagen, Boudy van (SAGE Publications, 2019)
Banana and plantain are one of the most important staple food crops and a significant source of income to smallholder farmers in the East African Great Lakes Region. Banana Xanthomonas Wilt (BXW) is a devastating bacterial disease that threatens smallholder production and livelihoods. We use a systems approach to describe how gender shapes roles and practices in the household, on the farm and in innovation processes. We draw on a case study in Burundi, where single disease stem removal (SDSR) has been introduced as a labour-saving package to reduce BXW incidence. Banana is grown by an estimated 90% of farmers, and BXW poses a critical threat to food security. We use qualitative data that include focus group discussions, interviews and transcripts from farmer learning group (FLG) discussions to describe gender norms, roles and practices and implications for awareness and uptake of SDSR in households. We identify gender patterns in innovation process, namely that men gain higher levels of access to information in FLGs than women and men are also primarily responsible for implementing SDSR. These patterns reflect gender-differentiated norms, roles and practices that are common in the household and in banana-based farming systems, thus demonstrating the ways that innovation processes perpetuate and reinforce common gender roles and practices. Women’s participation in FLGs, albeit lower than men, increases the potential of women to implement specific practices of the SDSR package. Systems approaches may be similarly used in different contexts where awareness and uptake of banana disease management packages, and other technical innovations, are not well understood. We found that gender norms, roles and practices significantly influence uptake of SDSR practices and warrant further investigation across the region, where smallholder uptake remains a pressing challenge to establish household food security.